THE CONSUMERS’ MORTGAGE PLAN: BASIS IN DEVELOPING A STRATEGIC FINANCIAL PROGRAM - D. Magtulis, Dale-Lorenz; T. Malibiran, Leonora; A. Sario, Jay (Penerbit Lafadz Jaya, 2024)
The objective of this study is to delve into the intricacies of consumers' mortgage plans and their pivotal role in the formulation of a strategic financial program. Given that homeownership stands as a significant milestone for individuals, a profound understanding of the dynamics of mortgage plans is indispensable for financial planners and policymakers alike. This research endeavors to unravel the key elements contributing to the development of an effective and strategic financial program centered around mortgage planning. The primary research questions guiding this study encompass the demographic profile of the respondents, an exploration of the factors influencing the extent of consumers' engagement, an assessment of the perceived effectiveness in developing a strategic financial program, and the proposition of a model for the development of such a program. Additionally, the study aims to discern patterns in consumers' decision-making regarding mortgages and to what extent these decisions align with the effectiveness of the strategic financial program. Through a comprehensive analysis of mortgage plans and consumer behavior, the study has revealed several key findings. It underscores the critical role played by dimensions such as Education on the Mortgage Planning Process, Credit Score Management, Mortgage Selection, Budget Determination, Risk Management, and Varying Economic Conditions on Mortgage Selection in shaping mortgage affordability. The research highlights the necessity for tailored financial strategic programs that align with individual preferences and long-term financial objectives. Furthermore, it underscores the importance of financial literacy and awareness in empowering consumers to make informed decisions about their mortgage plans. In conclusion, this study emerges as a valuable resource for financial professionals, policymakers, and individuals navigating the complex landscape of mortgage planning. By comprehending the nuances of consumers' mortgage choices, stakeholders can formulate targeted strategies to enhance financial well-being and promote sustainable homeownership.